2007
DOI: 10.1248/bpb.30.1150
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Activating Factor (PAF) Receptor Binding Antagonist Activity of the Methanol Extracts and Isolated Flavonoids from Chromolaena odorata (L.) KING and ROBINSON

Abstract: The leaf, stem and root extracts of Chromolaena odorata were evaluated for their effect on platelet-activating factor (PAF) receptor binding on rabbit platelets using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…The title plant has been reported to contain alkaloids, saponins, tannins, phlobatannins, anthraquinones, steroids, terpenoids, flavonoids and cardiac glycosides (Afolabi et al, 2007). Ling et al (2007) reported the presence of eleven flavonoids as the major group of compound and correlates the presence of these flavonoids in the ethanol extract of title plant with antioxidant and anti-inflammatory activity . Further protocatechuic acid is known to ameliorate STZ-induced toxicity in diabetic rats (Harini and Pugalendi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The title plant has been reported to contain alkaloids, saponins, tannins, phlobatannins, anthraquinones, steroids, terpenoids, flavonoids and cardiac glycosides (Afolabi et al, 2007). Ling et al (2007) reported the presence of eleven flavonoids as the major group of compound and correlates the presence of these flavonoids in the ethanol extract of title plant with antioxidant and anti-inflammatory activity . Further protocatechuic acid is known to ameliorate STZ-induced toxicity in diabetic rats (Harini and Pugalendi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SWE increased HO-1 at the transcriptional level, whereas stigmasterol may affect HO-1 expression at the translational level. It has been reported that SWE and its flavonoids exhibited inhibitory activity of platelet-activating factor (PAF) receptor binding [22]. The PAF is important mediator in the inflammatory response.…”
Section: Resultsmentioning
confidence: 99%
“…8) The antifungal, 9) and antiinflammation 10) of the plant extract were also investigated. Previous phytochemical investigations of this plant described the presence of flavonoids, [11][12][13][14][15] phenolics, 16) alkaloids, 17) terpenoids, 18) and essential oil. 19,20) Recently, chromomoric acids were isolated and showed significant effect on proliferatoractivated receptor (PPAR)-g activation.…”
mentioning
confidence: 89%